2023
DOI: 10.1001/jamanetworkopen.2023.9848
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Urologic Cancer Surgical Volume and Length of Stay During the COVID-19 Pandemic in Pennsylvania

Abstract: ImportanceDisruptions in cancer surgery during the COVID-19 pandemic led to widespread deferrals and cancellations, creating a surgical backlog that presents a challenge for health care institutions moving into the recovery phase of the pandemic.ObjectiveTo describe patterns in surgical volume and postoperative length of stay for major urologic cancer surgery during the COVID-19 pandemic.Design, Setting, and ParticipantsThis cohort study identified 24 001 patients 18 years or older from the Pennsylvania Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…This study showed a reduced LOS during the COVID-19 pandemic. This aligns with findings from multiple studies across different types of surgery which reported a similar reduction in LOH during the pandemic, including adult spinal deformity surgery [ 40 ], elective colorectal surgery [ 41 , 42 ], brain tumor surgery [ 43 ], bariatric surgery [ 44 ], and partial nephrectomy [ 45 ] without compromising surgical outcomes. Several factors may have contributed to this decrease.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study showed a reduced LOS during the COVID-19 pandemic. This aligns with findings from multiple studies across different types of surgery which reported a similar reduction in LOH during the pandemic, including adult spinal deformity surgery [ 40 ], elective colorectal surgery [ 41 , 42 ], brain tumor surgery [ 43 ], bariatric surgery [ 44 ], and partial nephrectomy [ 45 ] without compromising surgical outcomes. Several factors may have contributed to this decrease.…”
Section: Discussionsupporting
confidence: 83%
“…The pandemic increased the demand for hospital beds and shortening the hospital stay was a strategy to maintain the volume of surgery [ 44 ]. Patients may have also wanted to limit their hospital stays to reduce the risk of exposure to COVID-19 [ 40 , 45 ]. Moreover, patients were also more willing to follow hospitals’ recommendations than before the COVID-19 pandemic [ 40 , 46 ].…”
Section: Discussionmentioning
confidence: 99%